Predicting Staff Sexual Misconduct In Female Housing Units: Individual Versus Social Climate Factors - Robbins-Johnson, Hannah Mae (2014)
Staff sexual misconduct in prison has received increased attention since passage of the Prison Rape Elimination Act. As part of a larger investigation of violence and conflict in women's correctional facilities, over four thousand women prisoners from 15 facilities and 80 housing units rated the kinds of inmate and staff problems they felt existed in their housing units, including staff sexual misconduct. Due to the data being nested in housing units, we utilized multilevel regression analyses that regressed staff sexual misconduct scores on a range of individual and social climate variables. Social climate variables were found to be more influential in regard to inmate perceptions of staff sexual misconduct than were individual variables. Implications of the findings are discussed